PENGARUH FAKTOR INDIVIDU TERHADAP PERILAKU TIDAK ETIS AUDITOR INTERNAL PEMERINTAH PROVINSI BENGKULU - Fithria, Dinni; Aziza, Nurna; Aprila, Nila (UNIB Press, 2020)
The purpose of this research to examine the influence of the individual behavior on Government auditors internal unethical of Bengkulu Province. The population of the research is all auditors internal in inspector of Bengkulu Province amounting to 49 people. Analysis of data using analysis linear regression multiple. This study found: 1) the social factor influences of behavior unethical internal auditors inspector of Bengkulu Province. 2) Moral Reasoning influences behavior unethical internal auditors inspector of Bengkulu Province. 3) Emotional intelligence not influences behavior unethical internal auditors inspector of Bengkulu Province. 4) Intelligence spiritual not influences behavior unethical internal auditors inspector of Bengkulu Province. 5) Equity sensitivity not influence behavior unethical internal auditors inspector of Bengkulu Province. 6) Commitment Profesional infleunces behavior unethical internal auditors inspector of Bengkulu Province.